Evaluating prevalence, risk factors, and diagnostic techniques for Cryptosporidium infection in goats and surrounding water sources - Rafiq, Manahil; Khan, Naimat Ullah; Khan, Imad; Ahmad, Mansoor; Bibi, Aiman; Ben Said, Mourad; Belkahia, Hanène; Tariq, Muhammad; Saeed, Silwat; Abdel-Maksoud, Mostafa A.; El-Tayeb, Mohamed A.; Fatima, Sabiha; et al. (Frontiers in Veterinary Science, 2024)
BackgroundCryptosporidium spp. are protozoan parasites that infect the gastrointestinal tract of various animals, including goats, and can also contaminate water sources, posing a significant public health risk. Detecting Cryptosporidium oocysts in fecal and water samples is critical for understanding the epidemiology of cryptosporidiosis and implementing appropriate control measures. Various staining methods, such as the Modified Ziehl-Neelsen (ZN) and Kenyon’s Acid-Fast (KAF) staining techniques, are employed to identify these oocysts. This study compared the effectiveness of these two staining methods in detecting Cryptosporidium oocysts in goat feces and water samples across different geographic regions in district of Mardan, Khyber Pakhtunkhwa, Pakistan, and other factors such as genders, age groups, diarrheal statuses, and feeding regimes.MethodsA total of 300 fecal and 300 water samples were collected from goats and water sources in four geographic regions: Tehsil Katlang, Tehsil Takhtbhai, Tehsil Mardan, and Tehsil Lundkhwarh. Samples were categorized based on gender, age group (<1 year, 1–2 years, and >2 years), diarrheal status, and feeding regime (stall feeding, grazing). The two staining methods, ZN and KAF staining, were employed to detect Cryptosporidium oocysts. The detection rates were calculated, and statistical analyses were performed to compare the effectiveness of the two methods across different categories.ResultsThe overall detection rates of Cryptosporidium oocysts for fecal samples were 61.00% (95% CI: 55.22–66.55%) using the ZN method and 63.33% (95% CI: 57.60–68.79%) using KAF method, with no significant difference (p > 0.05). The highest detection rate was observed in Tehsil Katlang (70.66%) with the ZN method and in both Tehsil Katlang and Takhtbhai (66.66%) with the KAF staining method, having no significant difference (p > 0.05). Gender-wise analysis in fecal samples showed similar detection rates for males and females, with no significant differences. Age-wise, the highest detection rates were found in the youngest age group (<1 year) using the ZN method, and in the oldest age group (>2 years) using KAF staining, with no significant differences between age groups. Diarrheal status analysis indicated higher detection rates in diarrheic goats for both methods, with the highest detection rate in the diarrheic group of Tehsil Katlang (84.61%) using the ZN method. Feeding regime analysis showed no significant differences between stall-fed and grazing goats. For water samples, the detection rates of Cryptosporidium oocysts were significantly different between the two methods. The ZN technique had a significantly higher overall detection rate of 16.00% (95% CI: 12.03–20.64%) compared to 1.00% (95% CI: 0.20–2.89%) for KAF staining (p < 0.001). The performance of the two staining methods for the detection of Cryptosporidium oocysts in contaminated water samples from different geographic regions was also presented.ConclusionBoth ZN and KAF staining methods are effective for detecting Cryptosporidium oocysts in goat feces. However, in water samples, the ZN method showed a significantly higher detection rate compared to KAF staining method, suggesting its suitability for environmental surveillance. These findings highlight the importance of integrating reliable diagnostic techniques with public health interventions to mitigate the zoonotic risks of cryptosporidiosis.